PSYCHOLOGICAL DISTRESS AND EMOTIONAL PROBLEMS IN SCHOOL CHILDREN AFTER ARMY PUBLIC SCHOOL PESHAWAR INCIDENT - Nudra Malik; Amna Khawar; Bisma Ejaz; Naima Hassan; Javaria Haroon; Amina Muazzam (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The terrorist attack on Army Public School (APS), Peshawar, Pakistan on 16 December 2014 was one of the most horrifying incidents in the world with the highest death toll of children in the world. This dreadful incident left highly negative impact on the psychological and emotional health of school children. The purpose of the current study was to assess the psychological distress and emotional problems among school going children in response to this terrorist attack. A convenience sample of 100 boys and 100 girls with age range 11-16 years studying in 6th to 10th grade were selected from government and private schools of Lahore, Pakistan. Impact of Event Scale-Revised (IES-R), Pediatric Symptom Checklist (PSC) and a demographic sheet were used for collecting the data. Results revealed significant positive correlation between psychological distress and emotional problems in children. Independent sample T-test revealed that boys had significantly worse psychological distress and emotional problems than girls. It was concluded that traumatic incidents could lead to psychosocial problems in children and hence, appropriate interventions are necessary for enhancing the psychological wellbeing of children.